Structural heterogeneities around the megathrust zone of the 2011 Tohoku earthquake from tomographic inversion of onshore and offshore seismic observations. Issue 2 (19th February 2014) - Yamamoto, Yojiro; Obana, Koichiro; Kodaira, Shuichi; Hino, Ryota; Shinohara, Masanao
Abstract We performed a three‐dimensional seismic tomography around the coseismic slip area of the 2011 Tohoku earthquake. By combining data from the aftershock period collected by ocean bottom seismographs (OBSs), OBS data from previous studies off the Miyagi coast, and land seismic data, we modeled the detailed seismic velocity structure along the plate boundary from the Japan Trench to near the coastline. Our results indicate that VP, VS, and VP/VS along the plate boundary change drastically about 60 km landward from the trench axis. Trenchward of this boundary, velocities are consistent with a fluid‐rich environment (low VP and VS and high VP/VS) associated with the occurrence of sediment compaction and opal‐to‐quartz metamorphism. This area also corresponds to the contact between the slab and upper crust or between the slab and the sediment layer. A comparison of our results with numerical simulations and geological studies suggests that thermal pressurization might have occurred near the trench axis during the 2011 Tohoku earthquake. To the west of this boundary, where VP, VS, and VP/VS have moderate values, our model showed small‐scale heterogeneous structures in the subducted oceanic crust near the hypocenter of the Tohoku earthquake with regions of low and high VP/VS on the updip and downdip sides of the hypocenter, respectively. We interpret the former as corresponding to the strong coupling patch and the latter as the localized fluid‐rich zone. Small‐scale heterogeneities thus may affect the nucleation and rupture processes of large earthquakes.